160. Reduction in the Spread of Hospital-Associated Infections Among Pediatric Oncology Patients in an Animal-Assisted Intervention Program from a Canine Decolonization Procedure. (26th November 2018) - Dalton, Kathryn; Ruble, Kathy; DeLone, Alexandra; Frankenfield, Pam; Walker, Destiny; Ludwig, Shanna; Ross, Tracy L; Jaskulski, Janice; Carroll, Karen C; Rankin, Shelley; Morris, Daniel; Chen, Allen; et al.
Abstract: Background: Animal-assisted interventions (AAI), the use of animals as a complementary therapy in holistic patient care, has shown many positive outcomes. However, therapy animals can serve as mechanical vectors of hospital-associated infections (HAI), e.g., methicillin-resistant Staphylococcus aureus (MRSA). This pilot study assessed for transmission of HAIs among therapy animals, patients, and the hospital environment. We tested the effectiveness of a novel decolonization protocol for therapy dogs to reduce the risk of transmission of HAIs and enhance AAI program sustainability. Our hypothesis was that HAI transmission occurs from positive child to child, with the dog as an intermediary fomite. Methods: Before and after child–animal interaction, we sampled patients, dogs, and the environment, and collected vital statistics and survey data from patients. MRSA was detected in samples by culture and molecular testing. Therapy dog handlers performed normal pre-visit practices for 2 control visits, then switched to a decolonization protocol (chlorhexidine-based shampoo prior to the visit, and chlorhexidine wipes on the fur during the visit) for 2 intervention visits. Results: We evaluated 45 children and 4 therapy dogs over 13 visits. Children had decreased blood pressure and heart rate, and reported improved mental health scores post visit. MRSA conversion was identified from 10.2% of the children and 38.5% of the dogs, while 93% of the environmental samples were MRSA positive both pre and post. Patients that interacted closely with the dog had 8.01 times higher odds (95% CI 1.1–15.2) of MRSA conversion compared with patients who barely interacted with the dog. When stratified by intervention group, the MRSA conversation odds ratio of close interaction was 0.93 (95% CI 0.1–10.8) when the dog was decolonized versus 9.72 (0.9–99) when not decolonized. Conclusion: This study showed the potential for AAI visits to improve physiological and mental health of pediatric outpatients. A risk of HAI exposure to patients from interaction with the dog was found, but this effect was nullified by the decolonization procedure. Future research is needed to increase the safety of this valuable alternative therapy. Disclosures: All authors: No reported disclosures.